The Effect of Tunica Albuginea Incision on Testicular Tissue After Detorsion in the Experimental Model of Testicular Torsion - Gultekin, Aynur; Tanriverdi, Halil Ibrahim; Inan, Sevinc; Yilmaz, Omer; Gunsar, Cuneyt; Sencan, Aydin (Urology Journal, 2018)
Purpose: Testis torsion is a surgical emergency, and sometimes we cannot sufficiently prevent injury even surgical detorsion of the testis is performed in the appropriate time period due to some reasons such as tissue edema. In this experimental study, we investigated the effect of tunica albuginea incision (TAI) on testicular torsion-detorsion model (TDM). Materials and Methods: Twenty four male rats were used. The rats were randomly divided into three groups. In Group I, testicular torsion (TT) of 720° was created. After 4 hours of torsion period, the testis was detorsioned. Then three longitudinal incisions were made on tunica albuginea of the testis. In Group II, torsion and detorsion was created by the same way as in Group I, but TAI was not added to the procedure. Group III was Sham group. At the end of the first week, rats in the experimental groups were sacrificed and the testes were harvested for histological, immunohistological examinations and for the assessment of apoptotic activity. Results: In Group I, the procedures led to partial improvement in color of the testes. Modified Johnsen Scores in Groups I, II and III were detected as 7.8, 4.3 and 9.6 respectively (P = .001). In Group I, immunoreactivity of anti-APAF-1 was moderate in 7 rats, and strong in 1 rat. Immunoreactivity of anti-cytochrome C and anti-caspase 3 were moderate in 6 rats, and strong in 2 rats. Immunoreactivity of anti-caspase 8 and 9 were moderate in 5 rats, and strong in 3 rats. The differences of immunoreactivity between the groups were statistically significant. TUNEL percentages were detected as 40, 62% in Group I, 60% in Group II and 11,75% in Group III respectively (P = .001). Conclusion: As a result, multiple incisions made on tunica albuginea after detorsion in the TDM in rats, decrease the amount of ischemia- reperfusion injury. This effect might be related with the decrease in testicular edema and free oxygen radicals together with increase in tissue perfusion. Moreover, the decreased apoptotic activity seems to play a role in the decrease in inflammatory response and preservation of tissue parenchyma consequently.